Power to the people: The benefits and limits of employee self‐selection in organizations. (27th October 2021) - Ketkar, Harsh; Workiewicz, Maciej
Abstract: Research Summary: One of the key features of boss‐less organizations is self‐selection, where each employee is allowed to both initiate and join projects freely. While this approach has been gaining in popularity within many big and small organizations, we have a limited understanding of its properties, limitations, and key mechanisms. In this article, we analyze the efficacy and boundary conditions of employee self‐selection with respect to project selection and employee allocation. Our results suggest that the relative balance between an organization's human capital and the number of opportunities it faces plays a critical role in determining the advantages of self‐selection, which performs better when human capital is scarce relative to opportunities. We also examine common policies that organizations use to further improve the efficacy of self‐selection. Managerial Summary: Self‐selection or allowing employees to either launch their own or join existing projects freely, has been recently gaining in popularity. Companies across different industries have found this approach advantageous and have been pursuing it either across the entire organization, in selected units, or part time. In this article, we formally analyze the advantages and disadvantages of self‐selection and its different variants. We show that self‐selection is best pursued in organizations where the magnitude of opportunities outstrips available human resources. However, in environments where opportunities worth pursuing are in short supply relative to available employees, hierarchical arrangements tend to fare much better. We put forth a set of conditions that can help managers decide when self‐selection would be appropriate and when it may hurt performance.